U.S. presidential inaugurations - Santella, Andrew (New York Children's Press, 2002)
Discusses the history and traditions of swearing in the United States President, including inaugural events planned far in advance and those hastily prepared upon the sudden death of a president
American Corner
Includes bibliographical references (p. 46) and index
11
Keywords: Inauguration Day -- History -- Juvenile literature; Inauguration Day -- History; Presidents -- History; Presidents -- Inauguration; Presidents -- United States -- History -- Juvenile literature; Presidents -- United States -- Inauguration -- History -- Juvenile literature; Washington (D.C.) -- Social life and customs -- Juvenile literature; Washington (D.C.) -- Social life and customs